2000
DOI: 10.1107/s090904950000950x
|View full text |Cite
|
Sign up to set email alerts
|

Wavelength-dispersive double flat-crystal analyzer for inelastic X-ray scattering

Abstract: A double¯at-crystal analyzer for inelastic X-ray scattering is described. The general correlation between the energy and direction of the X-rays transmitted by the analyzer allows one to collect data for a range of energy transfers simultaneously. Such an analyzer with 120 meV resolution was built to operate at the copper K edge. Experimental results show that this X-ray optic can be an alternative to a conventional spherical-focusing backscattering analyzer in resonant inelastic X-ray scattering experiments o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The horizontal angle±energy dispersion shown in Fig. 3 is signi®cant for sources that are widely divergent in a plane that is perpendicular to the diffraction plane (Bortel et al, 2000). For incident radiation that is highly collimated in the horizontal plane (42 mrad for the source used here), there is negligible change in the resolution function from the zero-horizontaldivergence limit.…”
Section: Description Of the Opticmentioning
confidence: 87%
“…The horizontal angle±energy dispersion shown in Fig. 3 is signi®cant for sources that are widely divergent in a plane that is perpendicular to the diffraction plane (Bortel et al, 2000). For incident radiation that is highly collimated in the horizontal plane (42 mrad for the source used here), there is negligible change in the resolution function from the zero-horizontaldivergence limit.…”
Section: Description Of the Opticmentioning
confidence: 87%
“…Inelastic X-ray scattering spectrometers utilizing dispersion-compensation methods (Berthold et al, 1992;Suortti et al, 2001) and PSDs (Bortel et al, 2000;Tohji & Udagawa, 1987) have also been constructed earlier. Most interesting is perhaps the spectrometer of Hä mä lä inen et al (1995), where a cylindrically bent crystal was used instead of a spherical diced analyzer, and the utilized non-dispersive geometry corresponds to the use of the cube surface as an energy-analyzing element in the present experiment.…”
Section: Discussionmentioning
confidence: 99%
“…The remaining discussion in this section will revolve around the consequences of divergence perpendicular to the scattering plane (horizontal). A previous study showed (Bortel et al, 2000) that the transmitted energy E for rays having an angle # out of the principal diffraction plane is given by…”
Section: Analyzing Monochromatormentioning
confidence: 99%
“…Studies have therefore investigated the use of materials such as sapphire (Yavas et al, 2007) or quartz (Sutter et al, 2006) instead, but the poorer crystal quality of such materials has so far prevented their use in high-resolution instruments. Bortel et al (2000) realised the possibility of replacing the spherically bent backscattering analyzer with a high-resolution monochromator using two flat asymmetrically cut silicon crystals. Their device provided an energy resolution of 89 meV at an operating energy of 8.979 keV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation